Farmer Assessment of the Effectiveness of Empowerment Strategies to Increase Farming Profits - Hanggana, Sri (Universitas Muhammadiyah Yogyakarta, 2024)
Farmer empowerment is crucial for agricultural development, yet its effectiveness often depends on how well strategies align with farmers' needs. This research aims to determine the effectiveness of the farmer empowerment strategies according to the farmer assessment. The research employs a qualitative multi-case study approach, utilizing in-depth interviews and focus group discussions with farmer group chairmen and members. The study reveals varying levels of effectiveness across seven government-implemented empowerment strategies. These three strategies comprised developing agricultural product marketing systems, consolidating agricultural land, and providing access to science and technology were unfamiliar to participants. The organic fertilizer training strategy was deemed effective in improving competence and profits. Extension services were considered effective in enhancing competence, profits, and productivity. However, institutional strengthening strategies were seen as ineffective in developing farmer groups into cooperatives. Financing facilities through People's Business Credit (PBC).